2020
DOI: 10.1002/jcp.29845
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of carcinogenic signaling networks in endometrial cancer identifies RAB17 as a potential target

Abstract: Endometrial cancer is one of the most common malignancies in postmenopausal women. Several potential therapeutic targets have been investigated in current research, but few have been used clinically. Therefore, further investigating the potential pathogenesis of endometrial cancer and new effective therapeutic targets for endometrial malignancies is still necessary. Our study used a The Cancer Genome Atlas dataset and two Gene Expression Omnibus datasets for weighted gene coexpression network analysis to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…34 , 35 In the latest report, RAB17 was highly expressed in endometrial cancer, which regulated the cell cycle and promoted the proliferation of endometrial cancer by promoting the phosphorylation of AKT and mTOR. 36 In our study, we observed a significantly higher expression of RAB17 in paclitaxel-resistant ovarian cancer cells A2780/PTX and SKOV3/PTX in comparison with paclitaxel-sensitive ovarian cancer cells A2780 and SKOV3 for the first time. We conducted a systematic investigation.…”
Section: Discussionsupporting
confidence: 57%
“…34 , 35 In the latest report, RAB17 was highly expressed in endometrial cancer, which regulated the cell cycle and promoted the proliferation of endometrial cancer by promoting the phosphorylation of AKT and mTOR. 36 In our study, we observed a significantly higher expression of RAB17 in paclitaxel-resistant ovarian cancer cells A2780/PTX and SKOV3/PTX in comparison with paclitaxel-sensitive ovarian cancer cells A2780 and SKOV3 for the first time. We conducted a systematic investigation.…”
Section: Discussionsupporting
confidence: 57%
“…2A and 2B). Several well-known metastasis genes were included in the list of DEGs, including TCF7 (Zhao et al 2023 ), MAPK13 (Tan et al 2010 ), RAB17 (Zhou et al 2021 ), CXCL10 (Ka et al 2023 ; Lee et al 2022 ; Shang et al 2022 ), CTSK (Khan et al 2021 ; Li et al 2019 ; Wu et al 2022 ), CCDC80 (Huang et al 2023 ), and ABCC2 (Sensorn et al 2016 ). In line with RNA-seq analysis, our qRT-PCR confirmed the elevated expression of the aforementioned DEGs ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RAB17 is a small GTPase that belongs to the Rab family. The expression of RAB17 was initially reported to be specific to ECs [ 57 ], although it has recently been detected in melanocytes [ 58 ], hippocampal neurons [ 59 ] and macrophages [ 60 ], and cancer cells such as Hela [ 61 ], breast cancer [ 62 ], non-small cell lung cancer [ 19 ] and endometrial cancer cells [ 63 ]. RAB17 regulates basolateral to apical transcytosis and sustains polarized sorting [ 20 ], which is similar to polarization during tube formation, where ECs are polarized towards the basement membrane matrix [ 64 ].…”
Section: Discussionmentioning
confidence: 99%